10.2 Association of the history of maternal-placental syndrome and cardiovascular disease in women with systemic lupus erythematosus. (9th June 2014) - Soh, MC; Nelson-Piercy, C; Dib, F; McCowan, L; Westgren, M; Pasupathy, D
Abstract : Background: Young women with systemic lupus erythematosus (SLE) have a higher risk of cardiovascular disease (CVD). In unselected populations, maternal-placental syndrome (MPS) increases the risk of CVD. Aims: To determine if the history of MPS increases the risk of CVD in this high risk population. Methods: Using linked population-registries from Sweden, parous women with SLE were identified between 1973–2011. The outcome of interest was CVD, which encompassed coronary artery disease (CAD), stroke and peripheral vascular disease (PVD). MPS was defined as pre-eclampsia, small-for-gestational-age (SGA), placental abruption or intrauterine death (IUD). Multivariate analysis was performed adjusting for duration of SLE and maternal co-morbidities Results: There were 7, 410 pregnancies in 3, 977 women. The prevalence of CVD was 9% (n = 359), of which CAD accounted for 51.8% (n = 186), stroke 43.5% (n = 156) and PVD 18.9% (n = 68). MPS was not associated with CVD in multivariate analysis (adjusted OR1.2; 95% CI 0.9–1.5). The only features of MPS that were associated with CVD were IUD (adjusted OR1.8; 95% CI 1.0–3.3) and SGA (adjusted OR 1.4; 95% CI 1.0–1.9). Conclusion: Risk of CVD was not increased in women with SLE who had a history of MPS unless IUD or SGA occurred.